Maximizing the Use of e-Wallet (Ovo) for SMEs in Jakarta - Ika Febrilia; Rahmi, Rahmi; Mohamad Rizan (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
This activity is entitled "Maximizing the Use of E-Wallets OVO for UMKM in Jakarta". The object (target audience) of this activity is the UMKM players who have businesses in the Jakarta area. The activity was held in September 2020. The speakers who attended were representatives of the OVO platform. There are still many UMKM players who do not know the procedure or the use of digital wallets (especially OVO) in order to realize a cashless society. In addition, it was also found that UMKM players were not able to maximize the use of OVO to develop their own businesses. The solution offered is in the form of training for UMKM players regarding the OVO digital wallet, which is a procedure that can be done to become a merchant (if they are not already using it), as well as strategies that can be done to maximize the use of OVO in transactions (if they are already using OVO). The output target of this activity is a publication on journals and social media (YouTube and Facebook).